2D simulation of wave-particle coupling inspired by walking droplets. (9th May 2018) - Battaglia, Onofrio R; Fazio, Claudio
Abstract: In recent years, a fluid dynamics phenomenon has been observed that shows interesting analogies with several quantum mechanical ones. Under specific experimental conditions, a liquid droplet released on a vibrating liquid persists in jumping, forming a localized wave-particle, and its behaviour resembles that of a de Broglie wave-particle. In this paper we discuss a simplified model for this phenomenon and the results of numerical fluid dynamics simulations implemented on the basis of the model. In spite of the relevant simplifying assumptions of our approach, we observe that a wave-droplet coupling is obtained and the droplet travels at nearly constant velocity, as it is observed in experiments. This suggests that the model describes the basic features of the phenomenon well, and that the simulation could be used to introduce undergraduate students to the study of quantum mechanics.